The Evolving Strategy of Californium-252 Neutron Intracavitary Brachytherapy in Treating Patients With Low-Lying T2 or T3 Rectal Adenocarcinoma: From Fixed to Individualized Regime With Intrarectal Peritumoral Injection of Amifostine - Xiong, Yanli; Shao, Li; Liu, Jia; Zhou, Qian; Li, Chongyi; Liao, Maojun; Zhang, Lei; Dai, Xiaoyan; Li, Mengxia; Lei, Xin (Frontiers in Oncology, 2021)
Purpose: To retrospectively and comparatively evaluate the improvement of the efficacy and safety on the addition of 252Cf neutron intracavitary brachytherapy (ICBT), individualized or individualized with intrarectal peritumoral injection of amifostine (IPIA) to external-beam radiotherapy (EBRT) or concurrent chemo-EBRT in 314 patients with T2N0-1 or T3N0-1 low-lying rectal adenocarcinoma. Methods: Phase I: from 2009 to 2011, 157 patients were treated with additional 252Cf neutron ICBT for 4 fixed fractions with a total dose of 40-45 Gy-eq during the EBRT. Phase II: from 2011 to 2013, 75 patients were treated with individualized neutron ICBT delivered for 2-5 fractions with a total dose of 26-45 Gy-eq according to the response of tumor after concurrent chemo-EBRT. Phase III: from 2013 to 2014, 82 patients were treated with individualized ICBT protected by pretreatment IPIA. Results: The 4-year local control rates for entire T2 and T3 patients are 69.4%, 72.0% and 79.3%, while the 4-year overall survival rates are 63.1%, 54.7% and 72.0% (P=0.08), the 4-year disease-free survival rates are 55.4%, 52.0% and 69.5% (P=0.053) in Phase I, II and III, respectively . The late complication (LAC, ≥G2) rates are 33.8%, 26.7% and 15.9% respectively (P=0.012), the serious LAC (≥G3) rates are 4.5%, 4.2% and 0% respectively in Phase I, II and III. Conclusion: Concurrent chemo-EBRT combined with individualized 252Cf neutron ICBT protected by IPIA showed promising efficacy and safety in treating low-lying T2 and T3 rectal adenocarcinoma patients without surgery opportunity or willing.